The Oncology Specialist's Role in POLST Form Completion. (February 2018) - Lammers, Austin J.; Zive, Dana M.; Tolle, Susan W.; Fromme, Erik K.
Introduction: Patients with cancer and oncology professional societies believe that advance care planning is important, but we know little of who actually has this conversation. Physician Orders for Life-Sustaining Treatment (POLST) forms can help to document these important conversations to ensure patients receive the level of treatment they want. We therefore sought to determine the specialty of those signing POLST forms for patients who died of cancer to better understand who is having this discussion with patients. Methods: Retrospective cohort study including all deaths due to cancer in Oregon between January 1, 2010, and December 31, 2011. Death certificates were matched to POLST forms in the Oregon POLST Registry, and the signing physician's specialty was determined using the Oregon Medical Board's database. Results: A total of 14 979 people died of cancer in Oregon in 2010 to 2011. Of which, 6145 (41.0%) had at least 1 POLST form in the Registry. Oncology specialists signed 14.9% of POLST forms, compared to 53.7% by primary care, 15.3% by hospice/palliative care, 12.8% by advanced practice providers, and 2.7% by other specialists; 51.8% of oncology specialists did not sign a POLST form, whereas 12.5% completed 10 or more. Conclusion: Oncology specialists play a central role in caring for patients with cancer through the end of their lives, but not in POLST completion. Whether or not they actually sign their patients' POLST forms, oncology specialists in the growing number of POLST states should integrate POLST into their goals of care conversations with patients nearing the end of life.